Dimensions of the Burnout Measure: Relationships with shame- and guilt-proneness in neonatal intensive care unit nurses. Issue 2 (March 2022) - Barr, Peter
Abstract: Background: Burnout in neonatal intensive care unit (NICU) nurses has been correlated with personality proneness to shame. However, the structural validities of the one-factor Burnout Measure (BM) and the two-factor Personal Feelings Questionnaire-2 (PFQ-2) used to assess burnout and shame-proneness, respectively, in these nurses were not evaluated. Objectives: The aim of the study was (i) to perform factor analyses of the BM and the PFQ-2 and (ii) to determine the relationships of burnout dimensions retrieved by factor analysis with similarly validated dimensions of shame- and guilt-proneness in NICU nurses. Methods: This is a multicentre cross-sectional cohort study that involved 142 (24%) of 585 NICU nurses who were currently providing direct newborn care in six level 3–4 NICUs in New South Wales, Australia. Results: The BM was a multidimensional measure of burnout composed of three latent factors: demoralisation, exhaustion, and loss of motive. Based on burnout dimension mean scores of 4 or more, worryingly high levels of demoralisation, exhaustion, and loss of motive were reported by 21%, 84%, and 24% of nurses, respectively. Shame and guilt together explained 41%, 9%, and 15% of the variance in demoralisation, exhaustion, and loss of motive, respectively. Shame controlled for guilt made respective large and moderate contributions to the variance in demoralisation (β = .62, p < .001) and loss of motive (β = .33, p < .001). Guilt moderated the effect of shame on loss of motive (Δ R 2 = .031, p = .027). Conclusions: Factor analysis of the BM showed burnout in NICU nurses was a multidimensional syndrome comprising exhaustion, demoralisation, and loss of motive. Worryingly high levels of exhaustion, demoralisation, and loss of motive were not uncommon. The demoralisation dimension had a strong correlation with shame-proneness. Understanding the nature of demoralisation and the phenomenology of shame and guilt should be psychoeducational components of the holistic management of burnout in NICU nurses.